2010
DOI: 10.1002/pssc.200983241
|View full text |Cite
|
Sign up to set email alerts
|

Structural and optical properties of zinc oxide nanopowders doped with Mn

Abstract: Pure ZnO and Zn1‐xMnxO (x = 0, 0.02, 0.06, 0.10, 0.15) nanopowders have been synthesized by sol gel technique at low temperatures. XRD results indicate that the powder has a hexagonal polycrystalline structure without secondary phases. The nanopowders were characterized using the X‐ray diffraction (XRD) and transmission electron microscopy (TEM) observation. Kramers‐Kronig's analysis of mid‐IR reflectance spectra were employed to determine the doping effect on the optical constants and optical phonon modes fre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 17 publications
0
3
0
Order By: Relevance
“…Moreover, a shift of (1 0 1) peak positions to lower 2θ angles was observed. The increasing lattice constants ( a and c ) and the unit cell volume cause the shift in peaks' position to lower angles [40] . Several authors have reported the increase in both lattice constants, a and c , with increase Mn percentage.…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…Moreover, a shift of (1 0 1) peak positions to lower 2θ angles was observed. The increasing lattice constants ( a and c ) and the unit cell volume cause the shift in peaks' position to lower angles [40] . Several authors have reported the increase in both lattice constants, a and c , with increase Mn percentage.…”
Section: Resultsmentioning
confidence: 97%
“…The increasing lattice constants (a and c) and the unit cell volume cause the shift in peaks' position to lower angles. [40] Several authors have reported the increase in both lattice constants, a and c, with increase Mn percentage. They explain this fact taking into account that the radius of Mn 2 + (0.66 Å) is larger than that of Zn 2 + (0.60 Å), both in a tetrahedral configuration.…”
Section: Solid Characterizationmentioning
confidence: 98%
“…2 was dissolved in a scientific beaker having distilled water 250 ml under magnetic stirring for two hours, then 200 ml solution of Sodium hydroxide was added slowly under strong stirring at a pH of 12 [28,29].…”
Section: Experimental Methodsmentioning
confidence: 99%